Automatic traffic offences monitoring system at traffic light controlled intersection - Mangwaya, Gehas Gerald (Midlands State University, 2020)
Traffic monitoring is a very difficult task for traffic control department, especially in large cities. This prototype project is designed to monitor a traffic light controlled intersection by using a camera, whenever a vehicle breaks the traffic rules the camera takes a snap shot. Cameras are devices that, when linked to the signal controller, automatically photograph vehicles that enters the intersection after the onset of the red light. Typically offending drivers enter the intersection 12seconds after the onset of the red and most cameras are set to start photographing the drivers upon the 2esecond after red. Red light cameras are used to improve safety at traffic-light controlled intersections. Typically, the cameras are installed at high-accident intersections or0at0locations where drivers are likely to disobey traffic signals. Using sensors, the vehicles are monitored with reference to the traffic light indicators. A proximity induction sensor always on and if a vehicle exceeds the control line on the road, after RED light is on, the camera switches on and the images are stored in Windows Media file. The authority can view the images from a remote computer.